An investigation into the effectiveness of teacher turnover in the subject of geography: a case study of Kutama Day High School. - Chimbwanda, Vimbai Marcia (Midlands State University, 2018)
It is beyond doubt that teachers are the most deep-seated resource for improving pupils’ learning. For that reason, there is need to retain qualified teachers in all subject areas. Teacher turnover in the Geography department at Kutama Day High School has been influenced by demographic, uncontrollable and controllable factors. The most affected by these factors are the new and young teachers. Other factors that have affected pupils’ performance include dropping out of students, failure to pay examination fees by students and psychological immaturity. This study drew on a qualitative inquiry to investigate the effect of teacher turnover on pupils’ performance in the Geography subject. The target population comprised of teachers who had been part of this school during the past five years. Information was collected through interviews and document analysis. The high teacher turnover, inadequate resources in the Geography department, dropping out and psychological immaturity of learners has caused the inconsistent pass rates in Geography. The study recommends that the teacher – pupil ratio should be looked into when assigning workloads to teachers. The study also recommends that the Geography department should request for student teachers from teacher colleges every year as this will lessen the work load for the trained teachers. New teachers must be engaged in decision making, induction must be done every time a new teacher joins the school and responsibilities should be rotated to all teachers including the new teachers.